Comparative Aspects of Structure and Function of Cnidarian Neuropeptides - Takahashi, Toshio (Frontiers in Endocrinology, 2020)
Cnidarians are early-branching animals in the eukaryotic tree of life. The phylum Cnidaria are divided into five classes: Scyphozoa (true jellyfish), Cubozoa (box jellyfish), Hydrozoa (species, Hydra and Hydractinia), Anthozoa (sea anemone, corals, and sea pen), and Staurozoa (stalked jellyfish). Peptides play important roles as signaling molecules in development and differentiation in cnidaria. For example, cnidaria use peptides for cell-to cell communication. Recent discoveries show that Hydra neuropeptides control several biological processes including muscle contraction, neuron differentiation, and metamorphosis. Here, I describe the structure and functions of neuropeptides in Hydra and other cnidarian species. I also discuss that so-called primitive nervous system of Hydra is in more complex than generally believed.